Spirituality, Technology and Sustainability Islamic TourismIndustry: A Systematic Review - Halimah Zahrah; Ia Kurnia; Mega Sakova; Asep Suwarna; Dini Mardiani (IECON: International Economics and Business Conference, 2025)
The growth of Sustainable Islamic Tourism is closely linked to the increased use of smart technologies in tourist destinations. This paper explores how Smart Tourism Technologies can be integrated with Islamic values within the scope of sustainable tourism by applying Systematic Literature Review (SLR) and TCCM (Theory, Context, Characteristics, Methodology) methods. The analysis reveals that while technologies like Artificial Intelligence (AI) and Big Data are crucial in enhancing the tourist experience, the application of Islamic governance principles in these technologies remains underdeveloped. Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB) are frequently employed to examine how technology is adopted within the realms of halal tourism and medical tourism, but issues such as data privacy and security, which are vital for tourist satisfaction, have not been sufficiently addressed. Most research has been focused on Muslim-majority countries, yet interest in halal tourism and the adoption of smart technologies is expanding in non-Muslim countries, including China and South Korea. Although Smart Tourism Technologies are essential for enhancing tourist satisfaction and promoting tourism sustainability, there remain significant gaps in incorporating the social, cultural, and ethical dimensions of these technologies. Future research should concentrate on further understanding the role of Islamic values in tourism technologies and consider exploring innovative business models that could facilitate the creation of sustainable tourist destinations.